Carbon dioxide pipeline route optimization for carbon capture, utilization, and storage: A case study for North-Central USA. (June 2022) - Balaji, Karthik; Rabiei, Minou
Abstract: Carbon Capture, Storage and Utilization (CCUS) is a key activity used for reduction of carbon emissions while promoting sustainable transition of traditional power sectors to low-carbon economy. Carbon-dioxide pipelines are important for the proper and safe deployment of CCUS infrastructure. In this paper, a methodology is identified to map and optimize pipeline routes between various potential sources and sinks of carbon-dioxide in the North-Central region of USA. The methodology involves identifying areas for pipeline development between various important junctions using graph network theory. A mixed-integer program is formulated to identify the most economic deployment of CCUS infrastructure to achieve a defined carbon capture goal. The key contributions of this paper are the identification of cost-effective deployment strategies of pipeline in North-Central USA and the delineation of appropriate candidates for CO2 capture location and geologic storage sites. The novelty of this paper lies on the utilization of environmental & regulatory factors in determining CO2 pipeline routes and usage of mixed integer programming for choosing the most cost-effective infrastructure strategy for CCUS deployment. The pipeline routing strategy identified by the paper reducing overall length of CO2 pipelines. The results of the analysis indicate the influence of location as well as pipeline routes on the overall cost of CO2 avoidance.